Redesain Stadion Nasional La Patau di Kabupaten Bone - Iqbal, Nur; Sahabuddin, Wasilah; Alfiah, Alfiah (TIMPALAJA : Architecture Student Journals, 2022)
Abstract_ Bone Regency is one of the regencies in South Sulawesi which has a community with a high interest in football, coupled with the existence of a professional football club and registered as a member of the second caste of the Indonesian League, namely PERSIBO which is headquartered in a stadium located in Bone Regency. or known as the La Patau stadium, it should be necessary to revamp and improve the facilities and quality of the stadium both physically, in function, and in future prospects as a place for sports education, recreation and business in Bone district. La Patau Stadium is a stadium located in Maccanang, Tanete Riattang sub-district, Bone district, South Sulawesi province. La Patau Bone Stadium is a stadium built by the Government of Bone Regency in 2006 with a capacity of around 4000-5000 spectators. Seeing the current condition of the stadium where the number of stands capacity is not up to standard, the number of parking available in the stadium is not directly proportional to the capacity of the audience, there is no available parking for the player and official team buses, and there are still many supporting facilities that are not available so it should be redesigned. to La Patau Stadium on the basis of consideration of making changes or additions and structuring the interior and exterior of the building, with the increase in the audience stands, the number of rooms or facilities will also increase as needed so that this stadium meets the standards set by the Asian and international football associations Keywords: Stadium, Lapatau, Bone Regency